Ambient Constancy of Passivation-Free Ultra-Thin Zinc Tin Oxide Thin Film Transistor. (26th September 2015) - Liu, Li-Chih; Chen, Jen-Sue; Jeng, Jiann-Shing
Abstract : An ultra-thin (5 nm-thick), unpassivated zinc tin oxide (ZTO) thin-film transistor TFT, fabricated with solution process, exhibits a good field-effect mobility (13 ∼ 14 cm 2 /Vs), small subthreshold swing (∼0.30 V/dec.) and high on/off current ratio (∼10 8 ). The field-effect mobility can be further enhanced by increasing the ZTO thickness to 12 nm and 22 nm. Furthermore, ID -VG characteristics of the 5 nm-thick ZTO TFT remain unaffected, regardless of working in air (60% relative humidity), vacuum or dry O2 atmosphere. The dissimilar TFT characteristics are discussed in terms of oxygen deficiency content, as well as the Fermi level position (EF to EC ) for ZTO of various thicknesses to explain the moisture immunity of the 5 nm-thick solution-processed ZTO TFT.